2010
DOI: 10.1007/s10096-010-1061-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients with candiduria

Abstract: Candiduria is commonly encountered in hospitalized patients, particularly those with indwelling urinary catheters. While risk factors and therapy are well described in previous studies, little is known about long-term outcomes and recurrence rates of candiduria. We studied 188 patients with candiduria in a retrospective chart review at a single institution from January 1999 to December 2000. Data were collected regarding risk factors and underlying disease, therapy, follow-up cultures until December 2003, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
7
0
4
Order By: Relevance
“…Evidence. Asymptomatic candiduria has been followed long term, but no adverse consequences have been described [99]. Funguria resolved without specific treatment in 76% of a large ( N = 861) clinical cohort [100].…”
mentioning
confidence: 99%
“…Evidence. Asymptomatic candiduria has been followed long term, but no adverse consequences have been described [99]. Funguria resolved without specific treatment in 76% of a large ( N = 861) clinical cohort [100].…”
mentioning
confidence: 99%
“…Recent studies highlight the changing epidemiology of community and nosocomial candiduria [6,7,14,18]. Our data showed that C. albicans remained as the prominent species isolated from urine cultures in both community and hospital setting, 85% and 68% respectively.…”
Section: Discussionmentioning
confidence: 57%
“…Total ICUs bed capacity are 60. The patients were eligible if the urine sample yielded the growth of Candida species with a count of 10 3 colony-forming units (CFU) which is considered as candiduria [14]. For the isolate to be significant causing CUTI, the patient either had symptoms suggested of UTI supported by positive urine routine in patients culture without catheters, or in catheterized patients, two consecutive cultures of urine samples were positive for Candida species after changing the indwelling catheters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bei tiefen Infektionen, wie z. B. des Auges, der Herzklappen, des Gehirns oder bei einer hepatolienalen Candidiasis werden hingegen Azole oder liposomales Amphotericin B Keine Therapie (A II) e[155] Entfernung/Wechsel des Blasenkatheters (B I) d[155][156][157] Fluconazol (C I)[155] Blaseninstallation mit Amphotericin B (C II) f[158,155] Fluconazol (A II)[178] Liposomales Amphotericin B gefolgt von Fluconazol (A II)[179,180] Voriconazol (B II)[153] Caspofungin, gefolgt von Fluconazol (B II)[100] Posaconazol (C III)[181] Chirurgisches Débridement i[179] Tab. 3 Auszug aus den ESCMID-Guidelines für die verschiedenen Formen der Candida-Infektionen[20] doch eine zunehmende Rolle von erworbenen Resistenzen.…”
unclassified